Five Percent 5-Fluorouracil in a Cream or for Superficial Peels in the Treatment of Advanced Photoaging of the Forearms: A Randomized Comparative Study - Zerbini Guimaraes, Carolina Okada; Miot, Hélio Amante [UNESP]; Bagatin, Edileia (Wiley-Blackwell, 2014)
BACKGROUND The antimetabolite 5-fluorouracil (5-FU) is used for topical treatment of actinic keratosis. Overall improvement in the skin is also observed. Additionally, 5-FU was reported to be used for superficial peels.OBJECTIVES To evaluate the efficacy and safety of 5% 5-FU cream compared with peels for photodamaged forearms.METHODS This interventional, randomized, comparative, evaluator-blind study included 32 patients with severe photoaging of forearms. The regimens comprised either application of 5% 5-FU cream everyday for 4 weeks on 1 forearm and 4 weekly peels on the other. Efficacy assessment included: clinical photodamage scores, opinion of patients and investigators, and blind photographic evaluation by independent observers. Skin biopsies were performed for histologic and immunohistochemical analysis. Safety evaluation comprised observation of adverse events.RESULTS Clinical and histologic findings confirmed the benefits of topical 5% 5-FU, in cream or peels, which improved skin appearance and decreased the dermal elastotic material. Immunohistochemistry showed reduced levels of epidermal p53 and increase in the level of procollagen I. Results were maintained after 6 months. Predictable adverse events occurred, with no differences between treatments. Patients reported better tolerability to peels.CONCLUSION Five percent 5-FU cream or peels was safe and effective for the treatment of photodamaged forearms. Decreased epidermal p53 levels and new dermal collagen were confirmed.